The Importance of Watershed Studies: the Cintra Stream Micro-Watershed Model - Belluta, Ivalde; Marques da Silva, Assunta Maria; Serra Valente, José Pedro (Multiciencias, 1970)
Water quality in the Cintra Stream micro-watershed was assessed by means of analyses during 2 periods (June/2005-May/2006 and January/2007-December/2007), using bimonthly collections at 8 different sites, for the physical and chemical variables pH, NO3”“, NO2”“, BOD5, DO and TOC. This work aimed to study the anthropogenic effects on the Cintra Stream and their interrelations with soil occupation, polluting sources, water use and contributions to the water quality of two large bodies of water: the Tietê River and the Guarani Aquifer. To study the variables, variance analyses were followed by Tukey”™s test, at a 5% significance level. All studied parameters indicated that the stream shows self-depuration capacity starting at site 3 due to dilution, oxygenation of the water and consequent biodegradation of the existent organic matter. Corrective measures at sites 1 and 2 followed by preventive actions in agricultural areas (S3 to S7) will permit use of the stream water in the rural area.